Nassau Plantation : the evolution of a Texas-German slave plantation - Kearney, James C., 1946- (University of North Texas Press, 2010)
In the 1840s an organization of German noblemen, the Mainzner Adelsverein, attempted to settle thousands of German emigrants on the Texas frontier. Nassau Plantation, located near modern-day Round Top, Texas, in northern Fayette County, was a significant part of this story. This title highlights the relationship of German emigrants to slavery.